2021
DOI: 10.3390/pr9101690
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hydrogen Storage Kinetics and Cycling Properties of NaMgH3 by 2D Transition Metal Carbide MXene Ti3C2

Abstract: Metal hydrides have recently been proposed for not only hydrogen storage materials but also high-efficiency thermal storage materials. NaMgH3 contains a considerable theoretical thermal storage density of 2881 kJ/kg. However, its sluggish de/re-hydrogenation reaction kinetics and poor cycling stability exhibit unavailable energy efficiency. Doping with active catalyst into NaMgH3 is deemed to be a potential strategy to mitigate these disadvantages. In this work, the enhancement of de/re-hydrogenation kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Among these groups of materials, metal hydrides are the most attractive candidates due to their ability to achieve relatively high volumetric density. 30,[36][37][38] However, the gravimetric capacity does not meet the set target by DOE. 24 Moreover, metal hydride suffers from poor kinetics opting for charging time longer than the DOE target, 24 and requires high temperature for adsorption/desorption.…”
Section: Overview Of Hydrogen Energy Targetmentioning
confidence: 99%
“…Among these groups of materials, metal hydrides are the most attractive candidates due to their ability to achieve relatively high volumetric density. 30,[36][37][38] However, the gravimetric capacity does not meet the set target by DOE. 24 Moreover, metal hydride suffers from poor kinetics opting for charging time longer than the DOE target, 24 and requires high temperature for adsorption/desorption.…”
Section: Overview Of Hydrogen Energy Targetmentioning
confidence: 99%
“…This has been achieved by incorporating nanoparticles into MXene. In a study by Hang et al 95 , perovskite hydride (NaMgH 3 ) was introduced into the layers of 2D MXene. It has been observed that the presence of lamellar structures within the 2D MXene demonstrates the feasibility of achieving reversible hydrogen storage capacity (approximately 4.6 wt%) after five cycles.…”
Section: D-2d Nanocompositesmentioning
confidence: 99%
“…This technique has been spotlighted due to its high storage density, remarkable stability, and small space occupancy [33][34][35][36]. A number of metal hydride vessels have been developed [37][38][39]. NaAlH 4 , LiAlH 4 , LiBH 4 , NaBH 4 , and AlH 3 are used as metal hydrogen storage materials; in particular, Mg 2 NiH 4 is in the limelight because of its advantages, such as its high storage capacity, low cost, and light weight [40].…”
Section: Hydrogen Storage Techniquesmentioning
confidence: 99%